Differences in acceleration and high-intensity activities between small-sided games and peak periods of official matches in elite soccer players - Dalen, T.; Sandmæl, S.; Stevens, T. G.; Hjelde, G. H.; Kjøsnes, T. N.; Wisløff, U. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to compare whether the physical performance of players during 4 vs. 4 + goalkeeper (4 vs. 4) and 6 vs. 6 + goalkeeper (6 vs. 6) small-sided games (SSGs) is equivalent to those experienced during the most intense 5-minute period of soccer match play. Twenty-six male soccer players from an elite Norwegian league team took part. Players were monitored during 18 matches, 56 SSGs: twenty-eight 4 vs. 4 and twenty-eight 6 vs. 6 games. The ZXY Sport Tracking System was used to measure for each player the total distance covered, high-intensity running distance, sprint distance, number of accelerations, and player load (all expressed per minute). To compare the physical performance variables on players during the SSGs formats and match play, a 1-way analysis of variance with repeated measures was used. Players performed the same number of accelerations and player load in 4 vs. 4 (1.7 and 248, respectively) as in peak match (1.6 and 227, respectively), whereas in 6 vs. 6, there were 63% fewer accelerations and 15% lower player load (1.2 and 198, respectively), than in peak match. High-intensity running and sprint distance were significantly lower than mean match values in both 4 vs. 4 (4.1 and 0.2 m vs. 8.2 and 1.7 m) and 6 vs. 6 games (2.7 and 0.21 m vs. 8.2 and 1.7 m) (p < 0.05). In conclusion, only 4 vs. 4 SSGs are highly valuable, and in that, they elicit player load and accelerations to a level that is (at least) equivalent with peak periods of official match play.